Design and synthesis of photocrosslinker and light blocker based on L-Amino acid polyester and their application in solvent-free resin formulation for DLP/SLA 3D printing - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Asha, S. K. (Polymers, 2023)
Customising material design for new technological applications like additive manufacturing (AM) is a challenging yet promising approach to create a palette of materials suitable for developing eco-friendly products. LGlutamic acid and L-aspartic acid based aliphatic, photocurable polyester crosslinkers were designed and developed and incorporated into a solvent-free photocurable resin formulation with hydroxyl (ethyl)methacrylate (HEMA). Proof-of-concept 3D printing of clear and transparent objects was demonstrated using digital light processing (DLP) and Stereolithography (SLA) techniques. Resolution of the 3D printed objects could be improved by incorporating a Dansyl labelled L-glutamic acid polyester, which not only aided in modulating the viscosity of the resin formulation but could also function as a light blocker, thereby avoiding polymerization of unwanted areas while 3D printing. The curing kinetics of the photocurable formulation was analyzed using photo differential Scanning Calorimetry. Enzymatic degradability studies of 3D printed films were undertaken in PBS buffer containing esterase enzyme and compared with 3D printed samples using HEMA and a commercial crosslinker (Trimethylolpropane triacrylate (TMPTA)). Scanning electron microscopy (SEM) was used to evaluate the morphology of the 3D printed films before and after enzymatic degradation in the PBS buffer for 60 days. The 3D printed amino acid crosslinked films of HEMA presented high degree of degradation in contrast to the near total absence of any degradation in the 3D printed film crosslinked using TMPTA. The availability of new photocurable formulations that are enzymatically degradable are highly sought after for 3D printing applications.
Keywords: 3D printing; Crosslinker; L -Amino acid Polyester; Light blocker; Photocurable